Preconception lifestyle advice for people with subfertility - Anderson, Kirsty; Norman, Robert J; Middleton, Philippa (Cochrane database of systematic reviews, 2010)
Infertility is a prevalent problem and has significant consequences for individuals, families and the wider community. People's chance of having a healthy, live birth may be impacted upon by factors such as weight, diet, smoking, other substance abuse, environmental pollutants, infections, medical conditions, medications and family medical history. However, there is no current guideline about what preconception advice should be offered to people presenting for infertility treatment. It is important to determine what preconception advice should be given about these types of factors to such people in order to help them to make positive changes and hopefully improve their chances of conception and delivering a healthy, live baby. To assess the effects of preconception advice on the chances of a live birth for people who perceive that they may be infertile and are investigating the possibility of medical treatment to address subfertility. All published and unpublished randomised controlled trials addressing preconception advice to influence lifestyle factors in people who perceived that they may be infertile and investigated the possibility of medical treatment to address subfertility were sought from the Cochrane Menstrual Disorders and Subfertility Review Group Trials Register, Cochrane Central Register of Controlled Trials (CENTRAL), The Cochrane Library, MEDLINE, PubMed, EMBASE, PsycINFO, AMED, Cumulative Index to Nursing and Allied Health Literature (CINAHL), LILACS, trial registers for ongoing and registered trials, citation indexes, ISI Web of Knowledge, Clinical Study Results database, OpenSIGLE database, China National Knowledge Infrastructure (CNKI) Periodical Index and Google (inception to 5 October 2009). Only randomised controlled trials (RCTs), including cluster-randomised (group-randomised) trials, that considered preconception advice given to individuals who perceived that they may be infertile and were investigating the possibility of medical treatment from subfertility specialist services were eligible for inclusion. The primary outcome was live birth, defined as delivery of a live fetus after 20 completed weeks of gestation. Two review authors independently applied eligibility criteria to, extracted data from and assessed the risk of bias in the single included trial. One trial assessing smoking cessation advice for 94 infertile women smokers fulfilled the criteria for this review, but the trial did not report on the review's primary outcome of live birth or any other fertility-related outcomes. This trial of women attending a fertility clinic showed that smoking cessation advice tailored to a woman's "stage-of-change" (readiness to stop smoking) did not show significant evidence of a difference in stage (including smoking cessation rates) compared with standard clinical advice. No RCTs were located that assessed the effects of preconception advice on the chance of a live birth or other fertility outcomes in people who perceived that they may be infertile and were investigating the possibility of medical treatment to address subfertility. Given the lack of RCTs evaluating the effectiveness of preconception lifestyle advice for people in the afore-mentioned population, this review cannot provide guidance for clinical practice in this area. However, it does highlight the need for further research into this important subject.